GSTM1 copy number and promoter haplotype as predictors for risk of recurrence and/or second primary tumor in patients with head and neck cancer - Zhang X; Huang M; Wu X; Kadlubar S; Lin J; Yu X; Fan C; Ning B; Kadlubar FF (Dove Medical Press, 2013)
Xuemei Zhang,1 Maosheng Huang,2 Xifeng Wu,2 Susan Kadlubar,1 Jie Lin,2 Xinfeng Yu,1 Chunyang Fan,3 Baitang Ning,4 Fred F Kadlubar1†1University of Arkansas for Medical Sciences, Little Rock, Arkansas, 2The University of Texas MD Anderson Cancer Center, Houston, Texas, 3VA hospital, Little Rock, Arkansas, 4National Center for Toxicological Research, US Food and Drug Administration, Jefferson, Arkansas, USA†Fred F Kadlubar passed away on December 4, 2010.Abstract: The objective of this study was to determine copy number variant (CNV) and promoter genetic variants in glutathione S-transferase Mu class 1 (GSTM1) and the risk of recurrence (REC)/second primary tumor (SPT) in patients with previously diagnosed early stage head and neck cancer. Among 441 subjects, 133 experienced REC and/or an SPT, while 308 had single primary disease. TaqMan real-time polymerase chain reaction was used to measure the exact copy number of GSTM1 and direct sequencing was used to determine genetic variants in the GSTM1 promoter region. Multivariate Cox regression analysis was performed to estimate hazard ratios (HRs) and 95% confidence intervals (95% CIs) associated with copy number and genetic variants. REC/SPT-free survival times were compared by constructing Kaplan–Meier curves and differences between curves were tested by logrank test. Results showed a significantly decreased REC/SPT (HR = 0.57; 95% CI = 0.35–0.95) and longer REC/SPT-free survival in subjects with at least two copies of GSTM1 compared with the GSTM1 homozygous deletion, but not in those with one copy of GSTM1. The −498G, −426G, and −339T alleles were significantly associated with REC/SPT, with HRs of 0.11 (0.02–0.85), 0.28 (0.11–0.74) and 2.02 (1.07–3.82), respectively. Kaplan–Meier survival analysis showed that the −498G, −426G, and −339C alleles were also significantly associated with increased REC/SPT-free survival. Further haplotype analysis showed the haplotype P-498G--426G--339C carriers had decreased REC/SPT with a HR of 0.09 (95% CI 0.01–0.71) and increased REC/SPT-free survival compared with those with haplotype P-498C--426A--339T. The P-498C--426A--339T-containing reporter construct had significantly increased luciferase expression. These results suggest that the GSTM1 CNV and promoter haplotype are better predictors of REC/SPTs of head and neck cancer than just measuring the presence/absence of GSTM1.Keywords: GSTM1, copy number variant, REC, SPT, single nucleotide polymorphism